2006
DOI: 10.1108/02621710610684277
|View full text |Cite
|
Sign up to set email alerts
|

On the centrality of strategic human resource management for healthcare quality results and competitive advantage

Abstract: Purpose -Healthcare organizations have addressed current error issues by adopting quality programs, which usually include strategic human resource management (HRM). However, little research has focused on the determinants of successful quality programs at healthcare organizations. The purpose of this paper is to examine the centrality of strategic HRM for addressing healthcare errors, error reduction barriers, quality management processes and practices, quality program results, and competitive advantage. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 108 publications
1
24
0
2
Order By: Relevance
“…Only research by Gowen, McFadden, and Tallon (2006) focuses on health care and affirms that hospital errors can be successfully addressed with appropriate quality management processes, quality management practices and strategic HRM. However, there is no consensus about nature, content and drivers of HRM and there is no agreement on which practices should be incorporated (Boselie et al, 2005;Paauwe, 2009;Paauwe, Wright, & Guest, 2013).…”
Section: Quality Informationmentioning
confidence: 97%
“…Only research by Gowen, McFadden, and Tallon (2006) focuses on health care and affirms that hospital errors can be successfully addressed with appropriate quality management processes, quality management practices and strategic HRM. However, there is no consensus about nature, content and drivers of HRM and there is no agreement on which practices should be incorporated (Boselie et al, 2005;Paauwe, 2009;Paauwe, Wright, & Guest, 2013).…”
Section: Quality Informationmentioning
confidence: 97%
“…Their findings suggest that leadership based on charisma and inspiration at the highest organizational levels is associated with safety culture and adopting patient safety measures that are positively reflected in patient safety outcomes: e.g., reduced error-frequency, severity and impact, increased understanding and awareness. Gowen et al, (2006b) explored strategic HRM's impact on performance above and beyond adopting continuous quality improvement practices. They interviewed 587 hospital quality and risk directors and found that implementing both HRM and quality practices improved performance.…”
Section: Lean In the Health Sectormentioning
confidence: 99%
“…Gowen et al (2006:818) also suggest "…that hospital errors can be successfully addressed with appropriate quality management practices and strategic HRM". Gowen et al, (2006) found healthcare error sources are highly statistically and significantly related to quality management processes, quality management practices, and strategic HRM. They further suggest that the impact on sustainable competitive advantage is greatest for strategic HRM, which includes employee teams, training, information sharing, rewards, recognition, and promotion opportunity.…”
Section: High Performance Work Systems In the Health Care Sectormentioning
confidence: 99%
“…Gowen et al (2006) suggest that Strategic Human Resource Management (SHRM) can effectively address hospital errors in tandem with quality management processes and procedures. To date, there is a growing wealth of research investigating how SHRM practices can increase organisational performance and competitiveness in the private sector.…”
Section: Introductionmentioning
confidence: 99%